Curriculum and racism: curriculum analysis of bachelor’s programs in Performing Arts (Theater Education) in Higher Education (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article addressed the negligence regarding the inclusion of content related to African and Afrodiasporic cultures and Indigenous peoples in Higher Education, as mandated by Resolution n. 001/04 and Report n. 003/04 of the National Council of Education, as well as the lack of faculty training on these themes in universities, and the consequent challenges in implementing antiracist curricula. The main hypothesis is that the racism present in the country - disguised and legitimized by the Myth of Racial Democracy - forms the basis of a colonial thought that persists today through a whiteness project, which enables the violation of the Law and the denial of rights to a pluriepistemic curriculum.
Keywords: curriculum; racism; performing arts; racial democracy; whiteness